The edge of the water - George, Elizabeth, 1949- (Viking, an imprint of Penguin Group (USA), 2014)
Fifteen-year-old Jenn McDaniel's life on Whidbey Island becomes more complicated and her relationships with old and new friends take strange turns, partly due to the arrival of a woman researching a strange black seal.